Teachersâ€™ Evaluation on â€œSkillful 2 - Listening and Speakingâ€ - Le, Mai Xuan; Le, Thao Thanh; Nguyen, Quyen Thi Tu ((JELE) Journal Of English Language and Education, 2021)
There have been many reforms in English teaching and learning in Vietnam. Therefore, it raises a sufficient need for exploring the effectiveness of different coursebooks. This research is more qualitative than quantitative to investigate EFL teachers’ evaluation of the coursebook Skillful 2 – Listening and Speaking in a specific educational institution in the Mekong Delta of Vietnam. Six teacher participants using this coursebook partook in this study. Quantitative and qualitative data were collected by using two instruments, questionnaires and semi-interviews. The study provided a new checklist for evaluating materials in teaching and learning speaking and listening. The findings showed that (1) the strengths of the coursebook: e.g. the well-presented content page or the potential of building a strong English foundation of students’ proficiency; and (2) weaknesses of the book: via unimpressive cover page, the mismatch between the book’s content and the curriculum assigned in Vietnam, and the challenges found for teaching mixed-level classes. This study suggested some implications enhancing the effectiveness of sufficient materials for higher educational institutions.